Temperature responses of growth, photosynthesis, respiration and NADH:nitrate reductase in the cryophilic algae Koliella antarctica and "Chlorella" saccarophila, and in the mesophilic green alga Chlorella sorokiniana - V. ,VONA; V. , DI MARTINO RIGANO; LOBOSCO ,O.; CARFAGNA ,S.; ESPOSITO ,S.; RIGANO, C. (New Phytologist, 2004)
• Temperature effects on growth, photosynthesis, respiration and nitrate reductase (NR) were studied in the cryophilic algae Koliella antarctica and ‘Chlorella’ saccharophila , and in the mesophilic Chlorella sorokiniana . • Growth rate was measured as increase in optical density. Photosynthesis at saturating light and respiration in darkness were measured as O2 exchange. NADH : NR was assayed in crude extracts. • The two cryophilic algae grew below 15 °C, and C. sorokiniana above 20 °C. Photosynthetic and respiration rates of K. antarctica and ‘C .’ saccharophila were elevated at 5 °C, and peaked at 30 °C. Arrhenius plots from 5 to 25 °C were linear in K. antarctica , whereas in ‘C .’ saccharophila and C. sorokiniana they exhibited breaks at 15 and 20 °C, respectively. Values for activation energy (Ea) and the factor by which the rate increases with raising the temperature 10 °C (Q10) differed. Nitrate reductase had its optimum at 25 °C in cryophilic algae and at 35 °C in C. sorokiniana . • We conclude that growth of cryophilic algae at low temperature is favoured by elevated photosynthesis and respiration rates, but that it could be limited by a high respiration : photosynthesis ratio.